2019
DOI: 10.1002/pros.23864
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care and outcomes in small cell carcinoma of the prostate: A national cancer database analysis

Abstract: Background Small cell carcinoma (SCC) of the prostate is a rare, aggressive disease. Evidence is limited; however, the current standard of care is chemotherapy. The benefit of local treatment modalities is unknown. Methods We queried the National Cancer Database identifying all SCC/neuroendocrine cases of the prostate, excluding those with unknown nodal or metastatic status, unknown treatment, or those not receiving chemotherapy. Overall survival (OS) was calculated using Kaplan‐Meier curves. Multivariable Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Approximately 10–20% of CRPC cases treated with ARSi display a neuroendocrine phenotype 5 , 8 , 9 . CRPC-NE no longer responds to ARSi and carries a dismal prognosis, with a mean overall survival of 12 months and no specific standard of care treatment options available 10 . There is mounting evidence that CRPC-Adeno can transdifferentiate to an AR-indifferent state through a mechanism of lineage plasticity under specific genomic conditions, including but not limited to TP53, RB1 , and PTEN loss 4 , 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10–20% of CRPC cases treated with ARSi display a neuroendocrine phenotype 5 , 8 , 9 . CRPC-NE no longer responds to ARSi and carries a dismal prognosis, with a mean overall survival of 12 months and no specific standard of care treatment options available 10 . There is mounting evidence that CRPC-Adeno can transdifferentiate to an AR-indifferent state through a mechanism of lineage plasticity under specific genomic conditions, including but not limited to TP53, RB1 , and PTEN loss 4 , 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Rarely prostatectomy or radiotherapy alone have been shown to be curative because the tumor, in the majority of the cases, is metastatic (5), moreover, prostate SCC is usually not responsive to androgen deprivation and disease progression is not associated with rises in serum PSA values. In definitive, the best treatment remains the multidisciplinary approach by chemotherapy alone or combined with local therapy that could offer local palliation of clinical symptoms (5,10). In our case, the patient had a primitive prostate SCC characterized as locally advanced cancer involving bladder and kidney function in absence of documented distant metastases; therefore, we don't know if the patient died from prostate SCC or from concomitant onset systemic pathologies.…”
Section: Case Reportmentioning
confidence: 83%
“…In addition, molecular studies have reported an increased expression of gene involved in cellular proliferation, cell cycle, neuroendocrine differentiation and mitosis. Metzger et al (5) reported on 657 men with neuroendocrine SCC an overall survival of 12 months. Wang et al (9) on 260 patients selected from Surveillance, Epidemiology, and End Results (SEER) database showed an increased incidence of prostate SCC over time that was characterized by presence of high stage (stage IV in 77.7%), nodes involvement (49%) and distant metastases (68%) with PSA values greater than 10 ng/ml only in 23% of the cases; although patients underwent chemotherapy (58.8%), surgery (25.4%) and, radiotherapy (31.9%) the observed survival rates of 1-year, 2-year, and 5-year were 42.1%, 22.1%, and 12.5%, respectively.…”
Section: Case Reportmentioning
confidence: 99%
“…Seung Cho Lee and Robert A. Martienssen M icroRNAs (miRNAs) play important regulatory roles in the development of animals and plants, for instance by mediating gene expression and retrotransposon control 1,2 . They are generated through step-wise processing of primary miRNAs (pri-miRNAs) into precursor miRNAs (pre-miRNAs), but the synthesis mechanisms are complex and vary in different species.…”
Section: Competing Interestsmentioning
confidence: 99%